2014
DOI: 10.1128/jcm.03129-13
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Sa Select , a Chromogenic Medium for Detection of Staphylococci in Clinical Specimens

Abstract: bIn a preliminary study, known staphylococcus (n ‫؍‬ 86) and other microbial (n ‫؍‬ 12) isolates were plated on three chromogenic media, SaSelect (Bio-Rad, Hercules, CA, USA), CHROMagar Staph. aureus (CHROMagar Microbiology, Paris, France), and S. aureus ID (bioMérieux, Marcy l'Etoile, France). The sensitivities of all the media to detect Staphylococcus aureus after 24 h of incubation were high (100.0%). However, their specificities varied at 93.3% (95% confidence interval [CI], 86.0% to 100.0%) (CHROMagar Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…Microbiological methods employed are also variable [6]. For example, in this study we used chromogenic agar for the detection of MSSA and MRSA, which has been shown to have greater sensitivity than conventional culture methods [34].…”
Section: Discussionmentioning
confidence: 99%
“…Microbiological methods employed are also variable [6]. For example, in this study we used chromogenic agar for the detection of MSSA and MRSA, which has been shown to have greater sensitivity than conventional culture methods [34].…”
Section: Discussionmentioning
confidence: 99%
“…For the isolation of S. epidermidis, 50-100 mL of the culture were plated onto SaSelect culture plates (Bio-Rad Laboratories) and incubated at 37 C for 24 hours. Small and light pink colonies (Hirvonen et al, 2014) were picked randomly from the plates and verified on the MALDI Biotyper system (Bruker Corporation) according to the manufacturer's instructions. In general, from each skin swab, we aimed at obtaining $10 colonies annotated as ''S.…”
Section: Lead Contact and Materials Availabilitymentioning
confidence: 99%
“…Guided by our previous metagenomic data and a literature search 8,11,12,[14][15][16][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] , we compiled the aerobic and anaerobic cultivation conditions reported in Table 1 and Figure 1. To examine the proportion of microbes recovered by these conditions, we first characterized the fungal, bacterial, and viral composition of our samples using shotgun metagenomics as it is culture-independent and yields the most unbiased compositional reconstruction (Figure 2, Table S2).…”
Section: Cultivation Conditions and Species Identificationmentioning
confidence: 99%